2003
DOI: 10.1016/s0261-2194(02)00065-0
|View full text |Cite
|
Sign up to set email alerts
|

Baiting blackbirds (Icteridae) in stubble grain fields during spring migration in South Dakota

Abstract: Blackbirds (Icteridae) annually damage US$5-8 million of ripening sunflower in the northern Great Plains. Baiting blackbirds with avicide-treated rice during spring migration might reduce the regional breeding population. In March and April 1996-1997, we simulated a baiting program in eastern South Dakota to compare attractiveness of rice-baited plots placed in fields of corn and soybean stubble. Blackbirds used plots in corn stubble more often than plots in soybean stubble and chose rice-baited plots over unb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 5 publications
0
11
0
Order By: Relevance
“…1999). Blackbirds are also common in maize stubble where they forage for spilled kernels and weed seeds (Linz et al. 2003).…”
Section: Estimated Environmental Concentrationsmentioning
confidence: 99%
See 1 more Smart Citation
“…1999). Blackbirds are also common in maize stubble where they forage for spilled kernels and weed seeds (Linz et al. 2003).…”
Section: Estimated Environmental Concentrationsmentioning
confidence: 99%
“…Blackbirds typically slit open husks with their bills and puncture kernels in the milk stage (Steffey et al 1999). Blackbirds are also common in maize stubble where they forage for spilled kernels and weed seeds (Linz et al 2003). Therefore, the concentration of mCry3A in kernels was used to estimate the exposure of wild birds to mCry3A via cultivation of MIR604 maize.…”
Section: Wild Birdsmentioning
confidence: 99%
“…During the 1980s, DRC‐1339‐baited rice was successfully developed for baiting blackbirds in Louisiana to protect sprouting rice 8. In the following decade, DRC‐1339‐baited rice was used to develop baiting strategies for reducing the number of spring‐migrating blackbirds in North Dakota and South Dakota 5. The only two quantitative studies conducted in our study area showed that non‐blackbird (non‐target) use of rice‐baited plots in harvested corn fields was low 9, 10.…”
Section: Introductionmentioning
confidence: 94%
“…The study area was in Brookings, Miner and Lake counties in eastern South Dakota. This area was chosen because it is considered to be the most northern region where migrating flocks of blackbirds are large enough to warrant a baiting program 5. Eastern South Dakota lies in the Coteau Des Prairies physiographic region in the Central Lowland province 16.…”
Section: Study Areamentioning
confidence: 99%
See 1 more Smart Citation